E-038 Initial single center experience with the neuroform atlas stent. (22nd July 2018) - Hardman, J; Tsai, J; Witek, A; Moore, N; Rasmussen, P; Bain, M; Elgabaly, M; Hussain, M; Masaryk, T; Toth, G
Abstract : Introduction: Endovascular coil embolization of wide neck saccular aneurysms with stent assistance is a durable and effective technique. However, the majority of currently available stents require a large diameter deployment microcatheter. The Neuroform Atlas Stent (NAS) has just received FDA humanitarian device exception (HDE) for treatment of aneurysms measuring 2–4.5 mm. This stent has a low profile, and can be deployed through a 0.016 inch microcatheter. We review the technical success, and immediate efficacy and outcomes for patients treated with the NAS in our institution after FDA approval. Materials and methods: A retrospective chart review identified patients with wide neck aneurysms treated with the NAS from January to April 2018, after FDA humanitarian device exception approval. Patient demographics, data and angiographic imaging were reviewed for stent parameters and configuration, technical success, complications, hospital length of stay, pre and post treatment NIHSS and modified Rankin scores. Results: Twenty-seven NAS were deployed in 19 patients for 20 wide neck saccular aneurysms. There were 14 female patients (74%) with a mean age of 63.9 years. There were 5 male patients (26%) with a mean age of 60.4 years. Seventeen patients had elective unruptured aneurysm treatment, and 2 patients were treated for ruptured aneurysms. Stents were placed for both anterior and posterior circulation aneurysm locations: 10 at the anterior communicating artery, 3 basilar apex, 3 middle cerebral artery bifurcation, 2 A2/A3 anterior cerebral artery, 1 internal carotid artery terminus, and 1 in the posterior communicating artery region. The most common configuration was a single stent at the anterior communicating artery. A single stent was used for 14 aneurysms, and 2 stents each for the remaining 6 lesions. All stents were deployed successfully without technical complications. There were no intra-procedural stent-related complications. The average hospital length of stay for elective unruptured aneurysms was 1.4 days. There was no change in the admission NIHSS (range 0–1) or modified Rankin score (range 0–1) for any of the elective patients upon discharge. Follow-up evaluation after hospitalization was available for 5 patients at an average of 31±16.7 days, which found no change in their clinical status. Conclusion: Our early short term single center data after recent FDA HDE approval suggests that the NAS is safe and technically feasible for the treatment of wide neck aneurysms in anterior and posterior circulation locations. Further research is needed to determine the long term efficacy and safety of this device. Disclosures: J. Hardman: None. J. Tsai: None. A. Witek: None. N. Moore: None. P. Rasmussen: None. M. Bain: 2; C; Stryker consultant. M. Elgabaly: None. M. Hussain: None. T. Masaryk: None. G. Toth: None.